Bridgeless SEPIC Converter Based Computer Power Supply Using Coupled Inductor (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Switched Mode Power Supplies (SMPS) are used as power source for computers. Conventional SMPS used in computers are suffered by some serious problems such as poor power quality, high device stress, slow dynamic response, high harmonic contents, periodically dense, peak currents, distorted input current. To minimize these problems, a non-isolated bridgeless buck-boost single ended primary inductance converter (SEPIC) using coupled inductor is introduced at the front end of the SMPS, which is operated in discontinuous conduction mode (DCM). This proposed technique reduces the Total Harmonic Distortion(THD), which results in power factor improvement. The DC output voltage of the SMPS is almost a constant voltage which is regulated by means of the proposed SEPIC converter. For obtaining different dc voltage levels for the PC applications, the output of the front end SEPIC converter is fed to the half-bridge DC-DC converter. The output voltages of the SMPS are controlled by controlling any one of the output voltages. Design and simulation of the proposed converter are carried out using the MATLAB/simulink software.